What is Polypharmacy in Patients with Chronic Kidney Disease? A Systematic Review - Azhar, Al-Khulaifi (2023)
PurposePolypharmacy presents an increasing therapeutic challenge for physicians managing patients with chronic kidney disease (CKD). However, there is a lack of consensus regarding the specific medication count threshold that defines polypharmacy in this population. The objective of this review is to establish a unified definition of polypharmacy in the CKD population by examining the diverse definitions used in previously published studies. MethodsA comprehensive search was conducted in relevant databases (PubMed, SCOPUS, Cochrane, and disease-specific databases) from 2000 to May 2022 to identify studies with polypharmacy threshold definitions in patients with CKD. Studies meeting the inclusion criteria were included in this review, and their methodologic quality was assessed. FindingsFollowing the screening of the search results, duplicate records and studies that did not meet the inclusion criteria were removed, resulting in a total of 18 studies included in this review. Among these, 61.1% specified the polypharmacy definition to be a threshold of ≥5 medications. In addition, 22.2% specified a high polypharmacy definition at a threshold of ≥10 medications. However, none of the studies reported on the dichotomy between kidney-related and non-kidney-related polypharmacy. ImplicationsThis review indicates that a numerical threshold of ≥5 medications is commonly used to define polypharmacy in patients with CKD. Nevertheless, it remains uncertain whether a kidney-related polypharmacy definition or a high polypharmacy definition would better identify patients with CKD at risk for polypharmacy-related complications.